Gestational Weight Gain and Small for Gestational Age in Obese Women: A Systematic Review and Meta-Analysis. (11th January 2023) - Chen, Wen; Li, Beiyi; Gan, Kexin; Liu, Jing; Yang, Yajing; Lv, Xiuqin; Ma, Huijuan
Abstract : Objective . This systematic review and meta-analysis evaluates the relationship between gestational weight gain and the risk of small for gestational age in obese pregnant women. Methods . Studies were identified by searching the Web of Science, Embase, and PubMed databases up to June 30th, 2022. The meta-analysis was carried out to determine the risk of small for gestational age with gestational weight gain (GWG) below the 2009 Institute of Medicine (IOM) guidelines compared with within the guidelines in obese women. The Newcastle–Ottawa Scale was used to assess the methodological quality. The chi-squared test, Q test, and I 2 test were used to evaluate statistical heterogeneity. Subgroup analyses were conducted, and publication bias was assessed by funnel plots and Egger's test. Sensitivity analyses were performed for three groups of obese people (I: BMI 30–34.9 kg/m 2, II: BMI 35–39.9 kg/m 2, and III: BMI ≥ 40 kg/m 2 ) to examine the association of obesity and SGA. Results . A total of 788 references were screened, and 29 studies ( n  = 1242420 obese women) were included in the systematic review. Obese women who gained weight below the IOM guideline had a higher risk of SGA than those who gained weight within the guideline (OR = 1.27, 95% CI = 1.16–1.38, Z  = 5.36). Both weight loss (<0 kg) and inadequate weight (0–4.9 kg) during pregnancy in obese women are associated with an increased risk of SGA (OR = 1.50, 95% CI = 1.37–1.64, Z  = 8.82) (OR = 1.18, 95% CI = 1.14–1.23, Z  = 8.06). The same conclusions were also confirmed for the three obesity classes (I: OR = 1.38, 95% CI = 1.29–1.47; II: OR = 1.39, 95% CI = 1.30–1.49; and III: OR = 1.26, 95% CI = 1.16–1.37). Subgroup analysis by country showed that GWG below guidelines in obese women of the USA and Europe was associated with risk for SGA (USA (OR = 1.30, 95% CI = 1.15–1.46), Europe (OR = 1.24, 95% CI = 1.11–1.40)) and not in Asia (OR = 1.17, 95% CI = 0.91–1.50). Conclusion . Our findings indicated that obese pregnant women who had weight loss or inadequate weight (0–4.9 kg) according to the IOM guideline had increased risks for SGA. Moreover, we also evaluated that gestational weight loss (<0 kg) in these pregnancies was associated with an increased risk for SGA compared with inadequate weight (0–4.9 kg) in these pregnancies. Therefore, the clinical focus should assist obese women to achieve GWG within the IOM guidelines to decrease the risk for SGA.